The synthesis and liquid crystal behaviour of monosubstituted ferrocenomesogens - Imrie, Christopher; Loubser, Christa; Engelbrecht, Pieter; McCleland, Cedric W; Zheng, Yifan (Journal of organometallic chemistry, 2003)
The synthesis and characterization of several new series of monosubstituted ferrocenyl-containing liquid crystals has been achieved. The results indicate that a terminal ferrocenyl group can promote stabilization of a nematic liquid crystal state. At least three phenyl rings are required in the molecular core in order to provide nematic properties and addition of a fourth ring substantially enhances it. Bulky lateral substituents or the introduction of linker groups that introduce kinks inhibit liquid crystal phase formation. Short highly polarising terminal groups or terminal groups that support hydrogen bonding support liquid crystal behaviour. The synthesis of several new series of monosubstituted ferrocenyl-containing liquid crystals has been carried out. In molecules with a sufficiently large l/ d ratio, a terminal ferrocenyl group tends to promote stabilization of a nematic liquid crystal state. Bulky lateral substituents or groups which introduce molecular kinking inhibit the formation of liquid crystal phases.